2013
DOI: 10.2174/1570159x113119990037
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopment in Schizophrenia: The Role of the Wnt Pathways

Abstract: Objectives.To review the role of Wnt pathways in the neurodevelopment of schizophrenia. Methods: Systematic PubMed search, using as keywords all the terms related to the Wnt pathways and crossing them with each of the following areas: normal neurodevelopment and physiology, neurodevelopmental theory of schizophrenia, schizophrenia, and antipsychotic drug action. Results: Neurodevelopmental, behavioural, genetic, and psychopharmacological data point to the possible involvement of Wnt systems, especially the can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 296 publications
(294 reference statements)
3
27
0
1
Order By: Relevance
“…In addition to pathways enriched in differentially expressed genes (Wnt, Notch, Serine biosynthesis; Evgrafov et al, 2017), we found that PI3K-Akt signaling has been identified as important in multiple studies of SCZ (Mao et al, 2009; Panaccione et al, 2013; Singh et al, 2013; Topol et al, 2015; Mulligan and Cheyette, 2016; Howell et al, 2017; Wang et al, 2017). Pathway analysis of GWAS data, performed by The Network and Pathway Analysis Subgroup of the Psychiatric Genomics Consortium (2015) showed enrichment of several GO terms, associated with neuron structure and histone H3-K4 methylation.…”
Section: Methodsmentioning
confidence: 72%
“…In addition to pathways enriched in differentially expressed genes (Wnt, Notch, Serine biosynthesis; Evgrafov et al, 2017), we found that PI3K-Akt signaling has been identified as important in multiple studies of SCZ (Mao et al, 2009; Panaccione et al, 2013; Singh et al, 2013; Topol et al, 2015; Mulligan and Cheyette, 2016; Howell et al, 2017; Wang et al, 2017). Pathway analysis of GWAS data, performed by The Network and Pathway Analysis Subgroup of the Psychiatric Genomics Consortium (2015) showed enrichment of several GO terms, associated with neuron structure and histone H3-K4 methylation.…”
Section: Methodsmentioning
confidence: 72%
“…The most consistent abnormalities associated with antipsychotic response are Akt1, glycogen synthase kinase3beta and beta-catenin pathways [70]. VEGF is associated with inflammation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…However, alterations of Wnt canonical signaling pathway functionally lead to diverse neuropathologies and neurodevelopmental dysfunctions, such as altered synaptic plasticity, that have been reviewed by Inestrosa et al (2015) and Tang et al (2014) . Indeed, Wnt signaling pathway dysfunctions are involved in the etiopathogenesis of various neurological diseases such as chronic pain, cerebral ischemia, Huntington disease, amyotrophic lateral sclerosis and other neurodegenerative pathologies . Wnt alterations in schizophrenia could be through roles of this signaling pathway in neuronal migration, survival, and/or apoptosis .…”
Section: Discussionmentioning
confidence: 99%